2017
DOI: 10.1038/srep46550
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific synaptic plasticity improves the recognition of sparse patterns degraded by local noise

Abstract: Many forms of synaptic plasticity require the local production of volatile or rapidly diffusing substances such as nitric oxide. The nonspecific plasticity these neuromodulators may induce at neighboring non-active synapses is thought to be detrimental for the specificity of memory storage. We show here that memory retrieval may benefit from this non-specific plasticity when the applied sparse binary input patterns are degraded by local noise. Simulations of a biophysically realistic model of a cerebellar Purk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The focus on excitatory synapses also enables our work to be directly compared to studies of excitatory perceptron-like learning done on Purkinje cells-which have been classically conceived of as perceptrons (Marr, 1969;Albus, 1971)-, such as the work of Brunel et al (2004), Steuber et al (2007), and Safaryan et al (2017). These studies demonstrated that detailed models of Purkinje cells can learn to discriminate between different patterns of input from the parallel fibers (PF) via a perceptronlike usage of long-term depression (LTD), which is known to occur in PF-Purkinje synapses.…”
Section: Relationship To Models Of Learning In Purkinje Cellsmentioning
confidence: 99%
“…The focus on excitatory synapses also enables our work to be directly compared to studies of excitatory perceptron-like learning done on Purkinje cells-which have been classically conceived of as perceptrons (Marr, 1969;Albus, 1971)-, such as the work of Brunel et al (2004), Steuber et al (2007), and Safaryan et al (2017). These studies demonstrated that detailed models of Purkinje cells can learn to discriminate between different patterns of input from the parallel fibers (PF) via a perceptronlike usage of long-term depression (LTD), which is known to occur in PF-Purkinje synapses.…”
Section: Relationship To Models Of Learning In Purkinje Cellsmentioning
confidence: 99%
“…This work was important, as it provided a biologically relevant association between LTD and synapse elimination. In addition, studies also began to show that LTD of a synapse could also provide a meaningful way to increase storage capacity in neurons (Safaryan et al 2017), and increase the signal to noise ratio between synapses, without synapse elimination.…”
mentioning
confidence: 99%
“…However, metaplasticity was appointed as a role for NO only in a more recent study [Safaryan et al, 2017], where it was proposed as an appropriate candidate for implementing a type of plasticity that is non-specific and outperforms the standard plasticity model of pf -PC synapses. The model is based on the experimental evidence that plasticity requires the action of a diffusive and volatile second messenger able to induce plasticity in neighbouring non-active synapses, such as the NO.…”
Section: Modelling No Diffusive Plasticity In the Cerebellummentioning
confidence: 99%